Isolation, Media Optimization, and Industrial Application of Cellulase-Producing Bacteria from Coir Industry Waste soil - Eglin Juno B K; Dr. A L Hema Latha (The Bioscan, 2026)
Cellulases are crucial biocatalysts for the sustainable conversion of lignocellulosic biomass into fermentable sugars, enabling biofuel, paper, and textile industries to reduce their reliance on chemical processes. This study reports the isolation, optimization, and industrial application of cellulase-producing bacterial strains, Bacillus sp.